Caffeic Acid Induced Apoptosis in MG63 Osteosarcoma Cells Through Activation of Caspases - Ferry Sandra; Meta Ariyani Sidharta (Molecular and Cellular Biomedical Sciences, 2017)
Background: Caffeic acid has been reported that when it is combined with all-trans retinoic acid, it can inhibit proliferation activity of SaOS-2 or OSA-01 cells. In addition, caffeic acid merely could reduce cell viability of SaOS-2 cells. However, there is not any study in caffeic acid's possible effect to induce apoptosis in osteosarcoma cell.Materials and Methods: MG-63 cells were cultured in Dulbecco’s Modified Eagle Medium containing 10% fetal bovine serum. Cells were treated with various concentrations of caffeic acid. Apoptosis were analyzed with Sub-G1 assay and activation of caspase-8, -9, and -3 were analyzed with immunoblotting. Caffeic acid-induced percentage of apoptotic cells and cleaved-8, -9, -3 were then statistically analyzed.Results: Sub-G1 results showed that caffeic acid significantly induced apoptosis in MG-63 osteosarcoma cells in concentration dependent manner. Immunoblotting results showed that caffeic acid induced cleavage of caspase-8, -9 and -3. Cleaved-caspase-8 and -9 were increased at 1-hour treatment of caffeic acid, while cleaved-caspase 3 was increased markedly at 6-hours treatment of caffeic acid.Conclusions: Caffeic acid induces apoptosis significantly in concentration dependent manner through caspase-dependent intrinsic apoptotic pathway.Keywords: caffeic acid, osteosarcoma, MG-63, apoptosis, caspase